Perianesthetic risks in neonates and infants undergoing emergency gastrointestinal surgery - YIN Hong, LIU Shuangmei, LIU Meng, WANG Eerdun (精准医学杂志)
Objective To analyze the complications occurring during the induction, maintenance, and recovery phases of anesthesia and the perioperative period in neonates and infants undergoing emergency gastrointestinal surgery. Methods A retrospective analysis was conducted on the clinical data of 196 neonates and infants who underwent surgery for acute abdomen at our hospital. These patients were divided into neonatal group (group N, age ≤30 days, 115 cases) and infant group (group I, age 30 days to 6 months, 81 cases). Data on general information, disease distribution, and intraoperative and postoperative complications were collected for both groups. Results There were significant differences between the two groups in body mass (t =-8.517,P<0.05), proportions of low body mass infants (χ2=64.909,P<0.05) and proportions of premature infants (χ2=10.657,P<0.05), concurrent congenital heart disease (χ2=5.210,P<0.05), and concurrent septic shock and metabolic acidosis (χ2=8.728,P<0.05). Children in group N were more prone to hypoxemia (χ2=4.123,P<0.05), hypothermia (χ2=8.792,P<0.05), and hypoglycemia (χ2=4.074,P<0.05) during the anesthesia maintenance period. In addition, group N exhibited a significantly greater need for respiratory support (χ2=5.474,P<0.05), a significantly higher incidence of multiple organ failure (χ2=5.474,P<0.05), and a significantly extended length of hospital stay (t=4.636,P<0.05) compared with group I. Conclusion The risks associated with perioperative anesthesia are high for neonates and infants undergoing emergency gastrointestinal surgery. Specifically, the risks of hypoxemia, hypoglycemia, hypothermia, and apnea are significantly higher in neonates than in infants. Special attention must be given to the respiratory risks during anesthesia management in neonatal emergency surgery.